2004
DOI: 10.1017/s0266467404001737
|View full text |Cite
|
Sign up to set email alerts
|

Habitat structure, wing morphology, and the vertical stratification of Malaysian fruit bats (Megachiroptera: Pteropodidae)

Abstract: This study investigated the vertical stratification of Old World fruit bats (Chiroptera: Pteropodidae) in relation to habitat structure and wing morphology, in a lowland Malaysian rain forest. In total, 352 fruit bats of eight species were captured within the subcanopy of the structurally complex old-growth forest during 72 306 m2 mist net hours of sampling. Fruit bat species that were grouped in relation to capture height were also grouped in relation to wing morphology – with those species predicted to have … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
43
0
3

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(49 citation statements)
references
References 27 publications
(25 reference statements)
3
43
0
3
Order By: Relevance
“…Possible under-representation of species which habitually fly within the forest canopy may have been offset by our intensive sampling on ridgetops however, as this occurred at the level of the forest canopy in the immediate vicinity due to the steep terrain surrounding ridgetops. The fact that pteropodids, for whom vertical stratification is known (Hodgkison et al 2004), were only caught on ridgetops would appear to support this suggestion.…”
Section: Inventory Completenessmentioning
confidence: 89%
“…Possible under-representation of species which habitually fly within the forest canopy may have been offset by our intensive sampling on ridgetops however, as this occurred at the level of the forest canopy in the immediate vicinity due to the steep terrain surrounding ridgetops. The fact that pteropodids, for whom vertical stratification is known (Hodgkison et al 2004), were only caught on ridgetops would appear to support this suggestion.…”
Section: Inventory Completenessmentioning
confidence: 89%
“…in Southeast Asia (Francis, 2008). Second, our mistnets and harp traps were set at ground level (up to six meters), and it is likely that species that forage and/or commute at greater heights were under-represented (e.g., Emballonuri dae, Molossi dae, Rhino pomatidae, Miniopteridae, Ptero pus spp., Dyaco pterus spadiceus, and Mega erops wetmorei) (Hodgkison et al, 2004a;Francis, 2008). Third, our surveys were conducted mainly during dry seasons and this may have limited the representation of phytophagous bats.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have shown that habitats with greater structural complexity support greater bird diversity [14][15][16]. This pattern is not only limited to bird communities but has also been observed in non-volant small mammals [17], ungulates [18], reef fish [19], arthropods [20] and bats [21,22]. However, statistical support for the species-habitat heterogeneity relationship is biased towards vertebrates and habitats under anthropogenic influence [2] and varies among taxonomic groups.…”
Section: Introductionmentioning
confidence: 95%